Multiple Myeloma: Front Line Therapy and Autologous Stem Cell Transplantation - Kumar, Lalit (Annals of the National Academy of Medical Sciences (India), 2018)
Prognosis of multiple myeloma (MM) has improved during the past two decades. This has been attributed to the better understanding of the biology of disease leading to introduction of two new classes of molecules, namely immune-modulators (e.g. thalidomide, lenalidomide), and proteasome inhibitors (e.g. bortezomib), use of high dose chemotherapy and autologous stem cell transplantation (ASCT) and better supportive care. Current management of myeloma for young patients (≤65 years) includes initial induction therapy followed by consolidation with ASCT followed by maintenance therapy with low dose thalidomide or lenalidomide or bortezomib for 1-2 years.The choice of initial therapy for patients of MM is based upon their eligibility for ASCT which in turn is based on their age and major co-morbid conditions pertaining to cardiac and renal systems. Patients who are ≤65 years of age (or 65 to 70 years) with no major co-morbid conditions are considered potential candidates for ASCT. Four cycles of induction therapy are administered; a combination of 3 drugs (bortezomib, thalidomide, and dexamethasone (BTD) or bortezomib, lenalidomide, and dexamethasone (BLD) or bortezomib, cyclophosphamide and dexamethasone (BCD) is associated with higher complete response (CR) (approx. 30-40%) and very good partial response (VGPR) and better progression free survival (PFS). Further consolidation with ASCT results in CR rates of 50%–70%; patients who achieve CR, have improved event-free and overall survival. Our initial experience with 225 ASCT supports these observations.It is now possible to individualize therapy in a given patient. For example, for patients with renal failure (present in 20-30% of patients at diagnosis) ––bortezomib, dexamethasone and/or doxorubicin combination could be an option; for patients with pre-existing peripheral neuropathy––lenalidomide and dexamethasone is preferred; for patients at high risk of venous thrombo-embolism bortezomib- based regimens can be used safely. Treatment with bortezomib or bortezomib + lenalidomide for patients with poor cytogenetics (chromosome deletion t(4;14), t(14;16), 17p–) appears to result in an outcome similar to that in patients without these abnormalities.In conclusion, from being incurable, myeloma is now a chronic illness. Along with earlier diagnosis, improved treatment and better management of complications have resulted in longer disease control and survival with a better quality of life. Novel agents have provided an opportunity to tailor therapy in an individual patient. Further research is needed to improve outcome for patients who fail to achieve complete response, those with ISS stage III, and extra-medullary disease. Availability of oral proteasome inhibitors and monoclonal antibodies (e.g. IL-6 receptor) are likely to expand choice of agents for maintenance therapy in future.